Peran Guru PPKn, Partisipasi Pol Peran guru ppkn dalam menumbuhkan partisipasi politik pemilih pemula di man 1 pontianak - Pamilu, Suryo; Achmadi; Atmaja, Thomy Sastra (Program Studi PPKn, Fakultas Keguruan dan Ilmu Pendidikan Universitas Buana Perjuangan Karawang, 2024)
The purpose of this study was to determine the influence of PPKn teachers in encouraging political involvement of students as first-time voters. The researchers used qualitative research techniques that include a descriptive approach. Data collection methods include interviews, observations, literature reviews, and documentation. The data analysis approach consists of three steps: data reduction, data presentation, and inference. Credibility tests are used to assess the veracity of the data. The research findings revealed that: (1) the role of PPKn teachers in fostering student political participation as beginner voters through learning activities in MAN 1 Pontianak was carried out through the learning implementation plan (RPP), the implementation of PPKn learning, and evaluation of learning outcomes. (2) PPKn teachers play a role in fostering political participation of students as beginner voters outside the classroom by organizing election activities for Class Leaders, Study Group leaders, and student council leaders in MAN 1 Pontianak. In practice, the student council president is elected by majority vote, as well as the class president, and the head of the study group is elected by agreement.